2013
DOI: 10.1126/science.1240104
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Lamin-A Scales with Tissue Stiffness and Enhances Matrix-Directed Differentiation

Abstract: Tissues can be soft like fat, which bears little stress, or stiff like bone, which sustains high stress, but whether there is a systematic relationship between tissue mechanics and differentiation is unknown. Here, proteomics analyses revealed that levels of the nucleoskeletal protein lamin-A scaled with tissue elasticity, E, as did levels of collagens in the extracellular matrix that determine E. Stem cell differentiation into fat on soft matrix was enhanced by low lamin-A levels, whereas differentiation into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

138
2,116
4
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,661 publications
(2,330 citation statements)
references
References 123 publications
138
2,116
4
12
Order By: Relevance
“…1 c; refer to the Supporting Material for details). Recent work has shown that the nucleus is also viscoelastic, but the timescale of viscous relaxation is of the order of 1-300 s (14,15,19,20), which is an order of magnitude smaller than the time it takes the nucleus to pass through endothelial gaps/constrictions (3). Thus, the elastic properties we use here are the moduli after the viscous effects have relaxed.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 c; refer to the Supporting Material for details). Recent work has shown that the nucleus is also viscoelastic, but the timescale of viscous relaxation is of the order of 1-300 s (14,15,19,20), which is an order of magnitude smaller than the time it takes the nucleus to pass through endothelial gaps/constrictions (3). Thus, the elastic properties we use here are the moduli after the viscous effects have relaxed.…”
Section: Model Formulationmentioning
confidence: 99%
“…It has been shown that the levels of the NE proteins lamin A and C (lamin A/C) determine the stiffness of the nucleus (20,(31)(32)(33), and that lower levels of lamin A/C facilitate cell migration through tight spaces (8,10,34). We studied the influence of lamin A/C on transmigration by varying the modulus of the NE in our model (Fig.…”
Section: Ecm Stiffness and Gap Size Modulate Nuclear Transmigrationmentioning
confidence: 99%
“…From a structural perspective, the ECM has a fibrillar and viscoelastic character, and such biophysical features have been reported to have a significant influence on cell behavior [2][3][4] . Although the molecular pathways involved in cellular 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 mechanosensitivity are still open to investigation, it is well known that cells sense and respond to the stiffness of their environment by converting mechanical inputs into chemical outputs 5,6 . More recently, cell fate related to energy dissipation mediated by enzymatic ECM degradation has also been reported 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that YAP functions in a mechanosensitive pathway and responds to increased tension, extracellular matrix stiffness, and cell spreading (Dupont et al, 2011;Rauskolb et al, 2014;Swift et al, 2013). These and other data suggest YAP may act in a positive feedback loop where tension stimulates YAP activation, and YAP responds by increasing tissue tension (Calvo et al, 2013).…”
mentioning
confidence: 88%